α-Rhamnosyl-β-glucosidase-catalyzed reactions for analysis and biotransformations of plant-based foods - Minig, Paola Marisol (2011)
Most aroma compounds exist in vegetal tissues as disaccharide conjugates, rutinose being an abundant sugar moiety in grapes. The availability of aroma precursors would facilitate analytical analysis of plant-based foods. The diglycosidase α-rhamnosyl-β-glucosidase from Acremonium sp. DSM 24697 efficiently transglycosylated the rutinose moiety from hesperidin to 2-phenylethanol, geraniol, and nerol in an aqueous-organic biphasic system. 2-Phenethyl rutinoside was synthesized up to millimolar level with an 80% conversion regarding the donor hesperidin. The hydrolysis of the synthesized aroma precursors was not detected in an aqueous medium. However, in the presence of ethanol as a sugar acceptor, the enzyme was able to transfer the disaccharide residue forming the alkyl-rutinoside. The aroma precursors were significantly hydrolyzed (up to 3-4% in 2 h at 30 °C), which indicated the potential use of the enzyme for biotechnological applications, for example, in aroma modulation of fermented foods.